Pengaruh Penambahan Semen dan Variasi Serat Kelapa Pada Tanah Terhadap Uji Kuat Geser Langsung - Irviyanti; Irwan Lie Keng Wong; Ika Apriyani (Universitas Kristen Indonesia Paulus, 2025)
Soil stabilization is an effort to strengthen the soil's bearing capacity and shear strength. The aim of this research was to find the physical properties of the soil and the results of stabilization with a mixture of 5% constant cement and a mixture of 5%, 10% and 15% coconut fiber (length ± -10 mm) with direct shear strength testing. Data from tests on the physical properties of the soil that have been carried out in the laboratory, the AASTHO classification shows that the soil belongs to group A-2-7, and the results of the USCS classification of the soil are classified as silty sandy soil (SM). The results of direct shear strength testing in the soil mechanics laboratory showed that the addition of cement and coconut fiber increased the value of cohesion (c), shear angle (Ø), and shear strength (τ). The highest increase was produced in variations of 5% constant cement and 15% coconut fiber, with increased cohesion of 0.166 kg/cm² (point 1) and 0.168 kg/cm² (point 2), shear angles of 32.15° (point 1) and 32.50° (point 2), and shear strength of 0.367 kg/cm² (point 1) 0.371 kg/cm² (point 2). It can be concluded that the addition of cement and coconut fiber can help stabilize the soil at the landslide point.